Technical Translation in Nuclear Energy: New Terms, Context, Equivalence - Malynovska, Yu.; Vlasenko, K.; Ved, O.; Kovalchuk, V.; Bodrova, I. (Ядерна та радіаційна безпека, 2016)
The paper briefly outlines the theoretical concepts underlying scientific and technical translation such as equivalence and context. It emphasizes the importance of contextual knowledge essential for the translation of new terms that emerge in modern academic and technological society. The significance of extensive and comprehensive contextual knowledge is demonstrated by the example of two new concepts brought to light following the Fukushima Daiichi accident. The concepts and challenges associated with their translation are addressed in detail. Стисло викладаються теоретичні концепції, що лежать в основі науково-технічного перекладу, такі як еквівалентність і контекст. Підкреслюється важливість контекстуальних знань для перекладу нових термінів, які виникають у сучасному науково-технічному суспільстві. Значимість вичерпного розуміння контексту продемонстровано на прикладі двох нових концепцій, що виникли після аварії на АЕС «Фукусіма». Детально розглядаються самі концепції та пов’язані з ними питання перекладу Кратко излагаются теоретические концепции, лежащие в основе научно-технического перевода, такие как эквивалентность и контекст. Подчеркивается важность контекстуальных знаний для перевода новых терминов, возникающих в современном научно-техническом обществе. Значимость исчерпывающего понимания контекста продемонстрирована на примере двух новых концепций, возникших после аварии на АЭС «Фукусима». Подробно рассматриваются сами концепции и связанные с ними вопросы перевода.